2004
DOI: 10.1037/0090-5550.49.1.71
|View full text |Cite
|
Sign up to set email alerts
|

Proxy Efficacy: Implications for Self-Efficacy and Exercise Intentions in Cardiac Rehabilitation.

Abstract: Objective: To examine relations among proxy efficacy, exercise self-efficacy, and exercise in cardiac rehabilitation. Participants and Study Design: Twenty-nine cardiac rehabilitation outpatients (24 men and 5 women) enrolled in a 12-week hospital-based program. Measures of proxy efficacy and exercise self-efficacy, obtained in Week 3, were used to predict program attendance and exercise self-efficacy at Week 10. Late program (i.e., Week 10) exercise self-efficacy and proxy efficacy were also used to predict p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
39
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 20 publications
4
39
0
Order By: Relevance
“…These predictive 19 relationships between the tripartite constructs are at the heart of Lent and Lopez's (2002) 20 theoretical assertions. Moreover, the positive effect we forecasted for other-efficacy in relation to 21 self-efficacy is supported by existing research in exercise classes (Bray & Cowan, 2004;Bray et 22 al., 2001), as well as undergraduate educational contexts (Elias & MacDonald, 2007), whereby 23 psychology students have been shown to report greater confidence in their own ability when they 24 believe strongly in the capabilities of their faculty members. Similarly, with respect to RISE,be shaped by their estimations of their teachers' beliefs about them (e.g., Bouchey & Harter, 1 2005).…”
supporting
confidence: 85%
“…These predictive 19 relationships between the tripartite constructs are at the heart of Lent and Lopez's (2002) 20 theoretical assertions. Moreover, the positive effect we forecasted for other-efficacy in relation to 21 self-efficacy is supported by existing research in exercise classes (Bray & Cowan, 2004;Bray et 22 al., 2001), as well as undergraduate educational contexts (Elias & MacDonald, 2007), whereby 23 psychology students have been shown to report greater confidence in their own ability when they 24 believe strongly in the capabilities of their faculty members. Similarly, with respect to RISE,be shaped by their estimations of their teachers' beliefs about them (e.g., Bouchey & Harter, 1 2005).…”
supporting
confidence: 85%
“…According to Bandura (1997Bandura ( , 2001 and Lent and Lopez (2002), a strong sense of proxy efficacy should have a positive effect on self-efficacy. Our results are consistent with these ideas and add experimental evidence that supports previous correlational research showing positive correlations between proxy efficacy and self-efficacy in CR (Bray et al, 2006;Bray & Cowan, 2004) as well as asymptomatic exercisers (Bray et al, 2001).…”
Section: Discussionsupporting
confidence: 94%
“…In an investigation of proxy efficacy in CR, Bray and Cowan (2004) used an adapted version of Bray et al's (2001) proxy efficacy measure and found cardiac patients who had stronger proxy efficacy in their interventionists' abilities reported stronger self-efficacy as well as intentions to continue exercising on their own after completing their CR program. In a more recent study.…”
Section: Introductionmentioning
confidence: 99%
“…SE has also been found to be positively associated with exercise in CR patients during (Blanchard et al., 2002; Evon & Burns, 2004) and after (Sniehotta, Scholz, & Schwarzer, 2005) CR. However, other research has found no significant relationship between SE and exercise in CR patients (Bray & Cowan, 2004; Jeng & Braun, 1997). For example, SE for exercise was not related to exercise during CR (Jeng & Braun, 1997).…”
Section: Introductionmentioning
confidence: 94%